Cost and return analysis of Van operation in the Municipality of Miagao, Iloilo - Alvizo, Marjorie Villanueva
Generally, this study aimed to evaluate or assess the profitability of van operation in Miag-ao. It specifically dealt with the cost and return structures of the said business., The study was conducted in the municipality of Miag-ao, which is one of the towns in the province of Iloilo. There were 11 respondents who are all van operators and at the same time members of the Miag-ao Association of Van Owners and Drivers, Inc. (MAVAD). Two of them owned or operate two vans, so in the data presented there were 13 vans. A one-shot survey using recall method was used as a source of data. An interview schedule was also utilized in gathering the needed data for the study. In analyzing the data, frequency distribution, percentage, ranking and weighted mean were employed. Likewise, cost and return analysis was used to determine the profitability of the van operation. Results of the study showed that almost half of the respondents have an age range of 30-40 years. Majority (73%) of them were males and already married. All van operators earned college degrees and have well-paying jobs. Roman Catholic was the dominant religion and most of them have or belong to medium family size.The cost and return analysis of the study showed that the average initial investment in the van operation was P 238,000. The total annual operating cost was P 434,366. Forty nine percent of it was paid for the salaries and allowances of the laborers. The annual gross revenue was P 505,210 with a net income (or pure economic profit) of P 70,844. Rate of return on investment was 30% and it will take 3.4 years for the business to recover its initial capital outlay. Based on the results presented, with positive net profit and gross revenue it is profitable to engage in this business venture.